THE VICTIM AS A FORGOTTEN FIGURE IN THE JUSTICE SYSTEM – A FEW REMARKS IN THE LIGHT OF PAST FORMS OF PUNISHMENT - Kania, Agnieszka (Review of European and Comparative Law, 2017)
This article focuses on selected problems regarding the evolution of the punishment process. The starting point remains the assumption that regardless of the historical period, every palpable form of injustice related to a violation of a certain area of goods has resulted in an intervention approved at the given moment in history. The study notes that in the early pre-state period, seeking a remedy for wrongdoing was a private matter of the victim (or their family or clan) who could in that wayavenge on their own the injustice they had suffered. The process of publicising criminal law that began at the end of the Middle Ages has marginalised the process role of a victim in the possibilities to seek the remedy. However, the vertical criminal law relationship has, over time, changed to some extent. The privatisation of the justice system – especially noticeable nowadays – makes it possible to see that consensual methods of resolving conflicts caused by an offence essentially contributed to the reversal of a certain historical process. That reversal was certainly intended to “reveal” the victim, and thus to return the conflict resulting from the offence to its “owners,” i.e. the perpetrator and the victim.